Maca peruana (Lepidium meyenii) causa reprotoxicidade em Caenorhabditis elegans - Pilissão, Luiz Eduardo Ben (2018)
Maca (Lepidium meyenii) is a plant that grows above 4000 meters in the Central Andes of Peru and has different varieties according to the color of the hypocotyl. According to the population, its medicinal properties are connected to fertility and vitality. Besides the beneficial effects related to sexual health, maca has also been widely used by those who wish to lose weight naturally and healthy. However, there are few scientific studies validating these uses. The objective of the present study was to evaluate the effects of aqueous extract of maca on reproduction, using Caenorhabditis elegans as an experimental model. The Peruvian maca from local commerce was obtained, from which an aqueous extract was obtained. The animals were treated and maintained at 20 ° C in NGM (nematode growth medium), seeded with Escherichia coli OP50. The worms (2000) were exposed to maca extracts at different concentrations (41.25, 123.75, 247.5, 330 μg / μl) in the L1 larval stage for 30 minutes in liquid medium containing M9 and free of bacteria. Survival and reproductive toxicity analyzes (egg laying, eggs per worm) were performed on NGM / E plates. coli, 48h after treatment. Biochemical assays were performed using a homogenate of the commercial treatments and kits. Statistical analysis was obtained by one-way ANOVA followed by multiple comparisons with Tukey's post-test. The results showed that maca caused a reduction in survival at all concentrations. In addition, the extract caused a significant decrease in litter size. Our results also show that the maca extract caused alterations in the lipid profile and expression of vitellogenins and interfered in a marked way in the physiological balance of the germinated lineage of the worm reproductive system. Therefore, it is concluded that the use of the extract of Peruvian maca in these concentrations in C. elegans has effects contrary to the attributed and expected effects of this vegetable, since maca is used because of its supposed benefits on vitality and fertility.